FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI MANTAP PADA IBU DI KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA TAHUN 2024 - Haitami, Fatma; Manurung, Jasmen (TOUR HEALTH JOURNAL, 2024)
Background: The continuous increase in the global population remains a serious issue, as it impacts various aspects of life. Based on data from the interim population projections for 2020-2023, Indonesia's population in 2023 reached 278.696 million This number shows a steady increase compared to 272.682 million in 2020 and 275.773 million in 2021 (BPS, 2023). This high growth rate will affect development, thus necessitating policies to limit it. In response, the government promotes the Long-Term Contraceptive Method (MKJP) program. Purpose: This study aims to analyze the factors associated with the selection ofpermanent contraceptive methods among mothers. Method: The research uses an analytical study with a crosssectional design, conducted in Damuli Pekan Village„ Kualuh Selatan District, North Labuhanbatu Regency, in 2024. The population consists of mothers of reproductive age who are contraceptive acceptors, with a sample size of 96 mothers. The sample was obtained using accidental sampling technique. Data collection was carried out through interviews with the help ofa questionnaire that had been testedfor validity and reliability. Data analysis was conducted using statistical tests, specifically the Chi-Square test. Results: The results show a relationship between education level, age, and knowledge with the choice of contraceptive methods among mothers who are contraceptive acceptors in Kualuh Selatan District, North Labuhanbatu Regency. Disscusion and Conclusion: It is recommended that contraceptive acceptors actively seek information about permanent contraceptive methods, including the advantages, benefits, xriteria for use, and other relevant information. Likewise, it is suggested that the head of the health center increases the role of healthcare workers in Simangalam Health Center, Kualuh Selatan, in providing health education about permanent contraceptive methods.